Mental health in India: Challenges ahead - Kishore, Surekha; Khapre, Meenakshi (Indian Journal of Community Health, 2016)
With the advent of latest technologies and rapid industrialization human beings have made advancement to a great extent, in the materialistic world. He has mechanized his instruments in such a sophisticated way so as to carry out complicated and heavy tasks in comparatively lesser time and utilizing lesser manpower. In this pursuit of progress, he became more and more ambitious which further led him to stressful life and to make compromises with his other aspects of life intentionally and sometimes unintentionally. One has to consider all the aspects of individual’s physical, mental, social and psychological angles which play an important role in maintaining the individual’s overall personality development as well as wellbeing so that he may lead a productive life. These factors along with the environmental and surroundings influences the behavior of individual. In the present day life though human beings may have progressed socially, economically and also intellectually but somewhere he tended to neglect his emotions, feelings, tolerance and above all there is a growing concern of loneliness amongst all age groups. There is an imbalance between the amount of stress a person takes up with the amount he can cope up with, which has led to increase in behavioral and mental health problems. Burden of mental disorders had risen over last few decades in general mental health is often equated with the cognitive and emotional wellbeing - it is all about the way one thinks, feels and behaves. Mental health, can also mean an absence of a mental disorder. Various factors which has led to the rise in mental health problems are - growing population, continuous stress, over exertion, high ambition, socioeconomic conditions, loneliness, drug abuse, expectations, competitions and failures etc. The list is unending. It has been observed that there is a growing concern worldwide among developed as well as developing nations regarding the rise in behavioral and mental health disorders. According to the World Health Organization, mental health is “a state of well-being in which every individual realizes his or her own potential, can cope with the normal stresses of life, can work productively and fruitfully, and is able to make a contribution to her or his community. WHO estimated that globally over 450 million people suffer from mental disorders. Currently mental and behavioral disorders account for about 12 percent of the global burden of diseases. This is likely to increase to 15 percent by 2020. Major proportions of mental disorders come from low and middle income countries. (1) In 2010, a study conducted in NIMHANS, Bangalore reported that the burden of mental and behavioral disorders ranged from 9.5 to 10.2 per 1000 population which is very low compared to western countries mainly due to underreporting. (2)